Parametric study of child restraint system in side impact crash /lcby Shasthri Sivaguru - Shasthri Sivaguru (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
Motor vehicle crashes has become the leading cause of death for children in many developed countries. Recent findings show that side impacts are nearly twice as likely to result in a child fatality as frontal impacts, regardless of restraint status or seating position. While most Child Restraint Systems (CRS) provide good protection in frontal impacts when used properly, side impact-testing is not yet mandated and has not been a main design feature for most car seats and boosters. From study of the injury mechanism, several factors have been identified to play a major role in the causation of injuries. These factors are grouped into three. The first classified as crash kinematics, include two factors which are the crash impact angle and the door intrusion effect. The second group is classified as CRS design which highlights the CRS pitch angle, the CRS shell thickness and the harness coefficient of friction. The third classification falls under CRS misuse of which the presence of shoulder harness slack is noted to be a major contributing factor. To date, these factors have not been collectively assessed qualitatively to establish degree of significance to injury criteria. In this work, a parametric study of the stated parameters is undertaken to ascertain the sensitivity of the CRS design with respect to oblique side impact at two standard velocities in consideration of intrusion. Owing to the preponderance of head injuries, the Head Injury Criteria (HIC) is investigated as the main response while other common injury responses such as Neck Forces, Neck Moment as well as Thoracic Acceleration are also investigated. The methodology comprises of three parts. The first part pertains to the numerical model development and validation of the crash simulation. The second part of the methodology comprises of mathematical model development using the Response Surface Method based on Design of Experiments technique. In the third part of the methodology, the parameter sensitivity is statistically assessed both qualitatively and quantitatively, by means of the Student's t-test from multi-liner regression data of the mathematical models. It is found that Thoracic Acceleration response is erratic in nature for side impact and is not quantifiable. The singular and cross interactive parameter sensitivity for the remaining responses namely the HIC, Neck Forces and Neck Moment are mapped and the ensuing trends for each parameter consideration are reported . Notably, across the models, the impact angle parameter is largely shown to be the most significant parameter. The findings here will serve as a useful reference towards the development of newer test procedures and safety standards in addressing safety concerns in oblique side impact crash in children.